Gender in local television news presentation: an analysis of TV news markets in the U.S. Northwest - Craig, Karly (Kansas State University, 2017)
Traditionally, men have been the primary face and voice of live broadcasting. Limited research has compared Designated Market Areas by news content. This study compared and analyzed gender representations between large and small market news programs in the Northwest region of the United States. Hard news stories are those which audiences expect to be included in a newscast and are more likely time-sensitive. Soft stories, on the other hand, are those known to be not as crucial or time-sensitive as hard stories. The purpose of this study was to examine two major topics: (1) gender representation as news anchors and reporters, and (2) gender representation in types of stories covered. Data of gender representation was compared and analyzed between a large and small news market. Notable differences and similarities between both markets were revealed. This study found female news reporters present 16% more hard stories than male reporters even when females were underrepresented as overall news talent compared to male news talent. Males represented 55% of news talent compared to females at 45% of news talent. Male anchors also presented more news stories as overall news talent, indicating visible gender inequality in the presentation of news stories. Another important purpose of this study was to introduce a preliminary study by comparing and analyzing gender representation data by television market size. An important difference found regarding news anchors, was the large market sample more equally represented both males and females as anchors, whereas the small market sample did not. The data revealed a 56% disparity by exhibiting males 78% of the time and females only 22% of the time in the small news market. Both markets also displayed significant differences in the total count of news anchors, reporters, and news content.
Keywords: Anchors; Reporters; Designated market area; Northwest United States; News stories; Gender representation